2012
DOI: 10.7860/jcdr/2012/4686.2651
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Malformations in Perinatal Autopsies – A Study of 100 Cases

Abstract: Background: Congenital malformations remain a common cause of perinatal deaths and even though ultrasonogram can give fairly accurate diagnosis, perinatal autopsy is essential to confirm the diagnosis and look for associated malformations. Objectives:To emphasize the importance of perinatal autopsy in diagnosing congenital malformations and to compare the same with the prenatal ultrasound findings. Methods:The present study comprises 100 consecutive perinatal autopsies conducted after obtaining the approval fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…In the present study, autopsy diagnosis confirmed ultrasonographic findings in 54 cases (94.74%), among these in 27 cases (47.37%) it provided additional information, whereas primary diagnosis given by ultrasonography was changed in 3 cases (5.26%). The findings in the present study are similar to those of Sankar and Phadake et al [23,28] The most common system involved was musculoskeletal followed by central nervous system. Similar finding was noted by Potekar et al, 2013, [22] Tomatir et al 2009, [8] and Andola US et al 2012.…”
Section: Fetal Factorssupporting
confidence: 82%
See 2 more Smart Citations
“…In the present study, autopsy diagnosis confirmed ultrasonographic findings in 54 cases (94.74%), among these in 27 cases (47.37%) it provided additional information, whereas primary diagnosis given by ultrasonography was changed in 3 cases (5.26%). The findings in the present study are similar to those of Sankar and Phadake et al [23,28] The most common system involved was musculoskeletal followed by central nervous system. Similar finding was noted by Potekar et al, 2013, [22] Tomatir et al 2009, [8] and Andola US et al 2012.…”
Section: Fetal Factorssupporting
confidence: 82%
“…Similar finding was noted by Potekar et al, 2013, [22] Tomatir et al 2009, [8] and Andola US et al 2012. [23] Various combinations of systems involved in malformations were noted. This could be attributed to same embryological period of development of different systems.In this study the 13/57 (22.80%) cases showed multiple malformations occurring in single fetus or neonate.…”
Section: Fetal Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second most frequent abnormality in previous studies was either musculoskeletal system or urogenital system abnormalities as we also observed (7,9,10 Cardiovascular system anomalies are not easy to detect in the early weeks and in stillborn fetuses as the vascular structures are very fine and sensitive to dissection. Septal defects were the most frequent anomalies (45 of 88 cases) followed by complex anomalies in 27 cases, similar to the results of Ramalho et al (11).…”
Section: Discussionmentioning
confidence: 67%
“…The incidence for urogenital anomalies has been reported as 16.6%, [2] and 4.2 % by Favorito et al [8] Andola et al [9] have reported 20.45 % of renal anomalies in a study of 100 cases. In our study there were 3 cases (13.04%) having renal abnormalities in the form of nonascent and underdevelopment of one kidney, bilateral multicystic kidneys and bilateral renal agenesis in one fetus each.…”
Section: Discussionmentioning
confidence: 99%